Effective preparation of superhydrophilic-underwater superoleophobic nanoparticles/polymeric sponges for oil-water separation. (21st October 2020) - Lin, Bo; He, Wen-Xu; Jiang, Li-Wang; Li, Zeng-Tian; Wang, Hua-Ying; Wu, Ying-Xuan; He, Fu-An; Wu, Hui-Jun
Abstract: The hierarchically-micro/nanoscale rough surface structure and the high surface hydrophilicity are two necessary factors to construct the superhydrophilic-underwater superoleophobic materials for oil-water separation. In this work, an effective method on the fabrication of the superhydrophilic-underwater superoleophobic sponges was developed, in which the mixture of the Fe3 O4 nanoparticles or (and) the SiO2 nanoparticles, the chitosan, the polyvinyl alcohol, and the glutaraldehyde was coated on the polymeric sponge by dip-coating to obtain the surface-modified sponges possessing the rough superhydrophilic-underwater superoleophobic surface. The structure of the surface-modified sponges were investigated by TGA, FTIR, WAXD, XPS, SEM, two-dimensional EDS element mapping as well as VSM, and the underwater superoleophobicity of the surface-modified sponges was proved by CH2 Cl2 contact angle measurement. Furthermore, the resultant surface-modified sponges exhibited good oil-water separation ability by adsorption and filtration.